PENGARUH APLIKASI BIOCHAR TERHADAP PERTUMBUHAN Brassica rapa DI INCEPTISOL KAKI GUNUNG MARAPI DAN GUNUNG SINGGALANG - Nabila; Yulnafatmawita; Adrinal (JTSL (Jurnal Tanah dan Sumberdaya Lahan), 2026)
Inceptisol is a marginal soil type with low fertility, limited water retention, and an acidic pH, which poses challenges for horticultural cultivation, including chaisim (Brassica rapa var. parachinensis). This study aimed to evaluate the effect of biochar dosage on soil physical properties, soil pH, and chaisim growth in Inceptisol from three locations: Singgalang, Padang Lua, and Sariak. Five biochar dosages were used (0, 15, 20, 25, and 30 tons/ ha-1). The observed parameters included water percolation, soil pH, and fresh plant weight. Results showed that the 20 tons/ha-1 dose gave the best results by reducing water percolation by up to 4%, increasing soil pH from 6.38 to 6.42, and producing the highest fresh plant weight of 203 grams per pot, which was much higher than the control (11 grams per pot). The increased soil pH improved the availability of nutrients such as phosphorus, calcium, and magnesium, which are important for plant growth. However, the 30 tons/ ha-1  biochar dose caused soil pore saturation, reducing aeration and nutrient uptake efficiency, resulting in a lower fresh plant weight of 97 grams per pot. Combining biochar with NPK fertilizer also improved water use efficiency and nutrient availability. The effectiveness of biochar was further influenced by initial soil characteristics, with the best results found in soil from Singgalang.This study showed that biochar could be a sustainable soil management strategy to improve horticultural crop productivity on marginal tropical soils.